2001
DOI: 10.1002/1097-0142(20011115)92:10<2493::aid-cncr1599>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteasome level is a potential marker in patients with solid tumors and hemopoietic malignancies

Abstract: BACKGROUND Proteasomes are nonlysosomal proteolytic structures that have been implicated in cell growth and differentiation. Abnormal expression levels of proteasomes have been described in tumor cells, and proteasomes can be detected and measured in plasma. The objective of this study was to characterize differences in proteasome levels between normal, healthy donors and patients with neoplastic disease and to correlate the findings with clinical status and other biologic markers of disease spread. METHODS Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
73
2
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 25 publications
(26 reference statements)
8
73
2
4
Order By: Relevance
“…Similarly increased concentrations of circulating proteasomes were detected in plasma of patients with solid tumors, myeloproliferative and myelodysplastic syndromes (4 ), various autoimmune diseases (3 ), metastatic malignant melanoma or severe psoriasis (5 ), and critical illness with sepsis and trauma (6 ). Chemotherapeutic treatment of patients with acute leukemia decreased or even normalized concentrations of circulating proteasomes (2,4 ). Patients with chronic lymphoid malignancies had subnormal concentrations of circulating proteasomes, except for patients with progressing disease, who had increased concentrations (4 ).…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Similarly increased concentrations of circulating proteasomes were detected in plasma of patients with solid tumors, myeloproliferative and myelodysplastic syndromes (4 ), various autoimmune diseases (3 ), metastatic malignant melanoma or severe psoriasis (5 ), and critical illness with sepsis and trauma (6 ). Chemotherapeutic treatment of patients with acute leukemia decreased or even normalized concentrations of circulating proteasomes (2,4 ). Patients with chronic lymphoid malignancies had subnormal concentrations of circulating proteasomes, except for patients with progressing disease, who had increased concentrations (4 ).…”
mentioning
confidence: 81%
“…The finding that the concentration of circulating proteasomes increases dramatically in patients suffering from various diseases including autoimmune diseases (3,4 ) suggests that an increased amount of circulating proteasomes can be regarded as a marker of cells damaged under these pathologic conditions. We compared the pattern of proteasome subtypes in circulating proteasomes for patients with autoimmune disease with that found in healthy controls.…”
Section: Circulating Proteasomes From Patients With Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…While the concentration of plasma proteasome has been measured at between 2.1-2.4 g/mL [76], this is 300 times less abundant than inside cells [77]. Moreover, proteasomal degradation requires ATP which is around 1000 times less abundant extracellularly [78].…”
Section: Extracellular Protein Folding Quality Controlmentioning
confidence: 99%
“…Furthermore, several recent studies have indicated that the measurement of proteasome concentration in the serum or plasma using an enzyme-linked immunosorbent assay (ELISA) can be a new approach to diagnosis, prognosis and monitoring of anticancer treatment of patients with haematological malignancies and certain solid tumours [9][10][11][12]. The latest research has established that plasma proteasome concentration correlates with advanced disease in MM and that it may be an independent prognostic factor for survival [12].…”
mentioning
confidence: 99%